Leadership and talent development at the Mbombela local municipality - Qhibi, Tinyiko (My University, 2017)
Literature, which has been drawn for this research, defines talent development as a prime responsibility for leaders in an organisation to help achieve organisational goals and gain a competitive advantage. Further, talent development should be regarded as a collective approach which will encompass the other two parts of talent management, which is talent attraction and talent retention. Also, the integration of processes like change management, organisational culture and performance management has been outlined as beneficial factors to both employees and the company at large. While much has been written about talent management and talent development in particular, this study outlines what leadership can contribute towards a talent enriched organisation for future sustainability. Job satisfaction, visionary leadership and performance management are the three themes which emerged from this research. These themes require organisations to pay attention to them in order to achieve good results. What is also addressed is whether the focus of developing employees should be on the strengths or weaknesses of employees at individual level. However, the point not to be missed when dealing with the development of individuals in the workplace is to focus on TED (Total Employee Development). This helps the organisation to ensure that its workforce is equipped in all areas which is essential to achieve success and excellence. While organisations begin to accelerate talent development matters, they need to further focus on developing teams and this should be guided by the following principles: 1) to continue with the development of talented and experienced individuals to keep up with the changes in their respective fields; 2) paying attention to employees who are absolutely new and inexperienced in the field to help them develop interest in their work. The SRPD model (Specification, Raw Material, Production process and Distribution) has been drawn in as one of the tools which can be applied for the attainment of the desired 100% talent in the workplace rather than anything less which will be inadequate.
A research report submitted to the Faculty of Law, Commerce and Management, University of the Witwatersrand, in 50% fulfilment of the requirements for the Degree of Master of Management (in the field of Public and Development Management) March, 2017
Keywords: Leadership--South Africa; Personnel management--South Africa; Organizational effectiveness--South Africa; Local government---South Africa